Potential of Aqueous Extracts From Root Organs of Ratoon Plants Sorghum Cultivated on Inceptisols Soil as Bioherbicide - Andreani Kinata; Edi Susilo; Hesti Pujiwati (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This study aims to determine the best inhibitory effect of water extracts from the ratoon root organs of sorghum plants grown on Inceptisol soil on the germination of test plants. Methodology: The study used a single-factor completely randomized design with four treatments: control, Numbu roots, Super 1 roots, and Suri 4 roots. The experiment units were petri dishes, and the experiment was repeated four times. The bioassay method in petri dishes was applied, with 10 ml of water extract added to each dish, and 25 Vima 1 mung bean seeds were incubated for three days. Results: The water extracts from the ratoon roots of Numbu and Suri 4, as well as all other sorghum ratoon root extracts, significantly inhibited the germination of test plants compared to the control. Findings: Sorghum ratoon root extracts exhibit potent bioherbicidal properties. Novelty: This research provides insights into the allelopathic potential of different sorghum varieties. Originality: The study offers a detailed analysis of the bioherbicidal effects of sorghum ratoon root extracts on seed germination. Conclusions: Water extracts from sorghum ratoon roots, especially Numbu and Suri 4, effectively inhibit test plant germination. Type of Paper: Empirical Research Article